Fabrication of a Kagomé‐type MOF Membrane by Seeded Growth on Amino‐functionalized Porous Al2O3 Substrate. Issue 15 (19th June 2021) - Wang, Xiaoguang; Kusaka, Shinpei; Hori, Akihiro; Matsuda, Ryotaro
Abstract: In this study, we report an efficient fabrication method for the membrane of a metal‐organic framework (MOF) (Kgm−OEt) which is one kind of kagomé‐type MOF with a two‐dimensional (2D) sheet structure having one‐dimensional (1D) channels suitable for separation of H2 from other larger gases. The Kgm−OEt seed layer was created on an Al2 O3 substrate using layer‐by‐layer (LBL) growth, then a membrane was fabricated by secondary growth. The membrane on a 3‐aminopropyltriethoxysilane (APTEs)‐treated substrate obtained in this method was continuous and defect‐free with the crystal orientation suitable for gas transportation, while the membrane grown on an unmodified substrate was loosely packed with unfavorable crystal orientation. Abstract : A simple chemical modification for Al2 O3 substrate facilitates the preparation of a more compact and better‐oriented Kgm−OEt membrane.